Ana Kokkinos An Oeuvre of Outsiders - McWilliam, Kelly (Edinburgh University Press, 2019)
Ana Kokkinos is an Australian screenwriter, producer and director who has worked in film and television for almost thirty years. Best known for her fictional films - Antamosi, Only the Brave, Head On, The Book of Revelation and Blessed - her work is often bold and confrontational in its exploration of the alienation, estrangement and visceral distresses of those outside the mainstream. In the first major study of the director, Ana Kokkinos: An Oeuvre of Outsiders offers new readings of and across her fictional oeuvre by broadly tracing the deployment of the outsider as an organising motif.